Beginner's guide to cosplay armor and props craft epic fantasy costumes and accessories with EVA foam - Van den Goor, Joyce; Deguelle, Pascal (Salem, MA Page Street Publishing Co., 2023)
"Become the character you were destined to be! Joyce van den Goor, founder of Pretzl Cosplay, is here to guide you on your epic cosplay journey. Learn all the best tools, materials and trade techniques--such as sanding, shaping, detailing, painting and so much more--to craft standout armor and lightweight props out of EVA foam. Both cheap and easy-to-handle, this material is perfect for total newbies! With 22 different projects to test your skills, you're sure to impress at your next comic-con, Renaissance faire or live action role-playing event. From a medieval warrior's armor to a woodland elf's iconic ears to an enchanting sorcerer's handy spellbook, these pieces will serve as the perfect addition to your work-in-progress costume, or you can combine them all to create three full cosplay looks. Joyce provides traceable patterns for each project as well as detailed step-by-step images and plenty of ideas for variation. You'll find all of the large fold-out patterns conveniently included in the back envelope, while the rest are the perfect size for printing at home. Remember: It's dangerous to go alone! Take this comprehensive guide, and you'll have everything you need to bring your nerdiest dreams to life." --
An introduction to foam -- Crafting with foam -- The projects. Headwear ; Shoulder armor ; Arm and hand armor ; Torso and waist armor ; Leg and foot armor ; Props -- Resources and suppliers -- Index.
Includes index.
"Includes large fold-out patterns!" -- Cover.
112754
Keywords: Cosplay; Costume design; Armor; handbooks; Handbooks and manuals; Guides and manuels